Coordination between Actor in Handling Homeless People in Sidoarjo Regency - Miftakhurrokhmi Miftakhurrokhmi; Isnaini Rodiyah (Universitas Muhammadiyah Sidoarjo, 2022)
The high poverty rate in East Java can be explained by a variety of reasons, namely the lack of synergy in the poverty alleviation program between levels of government. So, the problem of poverty should be a top priority in development policy and also the main challenges in policy development in East Java, to achieve the welfare of the community. Causes of poverty is the lack of distribution of work, so the big cities in general provide more jobs and greater than small towns.This study aims to describe and analyze the condition of the tramp in Sidoarjo, as well as describe and analyze the synergy of actors in dealing with a tramp in Sidoarjo. This type of research is descriptive qualitative research. Determination of informants of this research using purposive sampling, with the informant Section Head of the Social Rehabilitation Department of Social Sidoarjo Regency, the Head of the Field of Public Order and Peace of the Community Civil service Police Unit of the City of Sidoarjo, Head of the Social Welfare Workers district in Sidoarjo, and the Tramp who roaming the streets. Data collection techniques in this study using observation, interview and documentation. The technique of analyzing data in this research using data collection, data reduction, data presentation and data verification. The results showed most of the bums in Sidoarjo is the immigrant population of the cities in the vicinity Sidoarjo and stay vagrancy, although there is also a drifter who comes to Sidoarjo in the morning to beg and go home at night. A variety of factors that affect the arrival of a vagrant to Sidoarjo, ranging from oppressed the needs of the economy, have hope for a better life in Sidoarjo up feeling lazy to work.